Analysing the Landscape Aesthetics in the Urban Context of the Kingdom of Bahrain - Huma Mohammad Khan; Dana Alkhan (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
Urban development in the Kingdom of Bahrain has been a rapid phenomenon. To overcome the urban challenges and progress in an effective manner, the Kingdom of Bahrain has undertaken several measures for sustainable development. Landscape aesthetics plays a vital role in achieving urban sustainability and affects human perception and behavior in the Kingdom of Bahrain. The residents of the Kingdom of Bahrain have predominantly enjoyed beach fronts due to its geographical location. However, recent urbanisation has resulted in the development of design elements that are not associated with the sea. This research aims to analyse the change in landscape aesthetics due to urbanisation and the impact of social and cultural factors on it. The methodology adopted in this research includes site visits, documentation, and surveys. The study contributes to understanding the changing landscape aesthetics in the Kingdom of Bahrain. It analyses the effect of social and cultural factors on the changing landscape aesthetics in the Kingdom.